Storm induced morphological changes in Carcavelos Beach, Portugal: contribution for coastal management - Oliveira, Filipa S. B. F. (2020)
Field data based information on the coastal sediment dynamics becomes even more relevant for coastal managers in the present context of climate changes. Due to the sea level rise and the increase of frequency and intensity of coastal storms, coastal managers need to implement effective and efficient solutions for increasing coastal resilience, namely through reprofiling the beach for restoring the sediment balance and providing space for the beach natural dynamics. The study characterises and quantifies the morphological changes in an Atlantic urban sandy beach under extreme wave energy and sea level conditions. The erosion of the foreshore and backshore of this particular beach was characterised as function of the intensity and duration of the hydrodynamic forcing parameters (waves and sea level). This 24-hour duration storm event, which delivered to the beach a total energy of 1.7x109 J, caused the seaward displacement by the undertow current of approximately 3x103 m3 of median well sorted sand from the beach foreshore and backshore.